Llakiq sonqokuna (Suffering hearts). Affinities and distances between Kilku Warak’a and Arguedas related to the harawi in the poetics of Yawar Para (Rain of blood) - Quispe Collantes, Roxana (2019)
Andrés Alencastre Gutiérrez (1909-1984), a bilingual writer known as Kilku Warak’a, is considered one of the most important poets of the Quechua language. I approach his biography, his written production, and his poetry written in Quechua. I review the notion of harawi for the analysis of the poem collection Yawar Para (Rain of blood). Arguedas pointed out that the poetry of Alencastre expresses a sensitivity mediated by the “Indian pain” and the “Mestizo anguish”, but his interpretation omits data he knew, such as his position as landowner and promoter of a learned Quechua (Qhapaq Simi). I conclude that the harawi of Alencastre can be defined as singular, distanced from the real needs and experiences of the runa.